2012
DOI: 10.1093/jxb/ers222
|View full text |Cite
|
Sign up to set email alerts
|

Selenite-induced hormonal and signalling mechanisms during root growth of Arabidopsis thaliana L.

Abstract: Selenium excess can cause toxicity symptoms, e.g. root growth inhibition in non-hyperaccumulator plants such as Arabidopsis. Selenite-induced hormonal and signalling mechanisms in the course of development are poorly understood; therefore this study set out to investigate the possible hormonal and signalling processes using transgenic and mutant Arabidopsis plants. Significant alterations were observed in the root architecture of the selenite-treated plants, due to the loss of cell viability in the root apex. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(80 citation statements)
references
References 60 publications
5
73
0
Order By: Relevance
“…Furthermore, the role of NO to promote Se concentration of rice seedling roots under Se IV supply was confirmed. Our data are consistent with the results of Lehotai et al () in the model plant Arabidopsis thaliana , but differ from those in Brassica rapa , in which Se itself triggered NR and NOS dependent generation of endogenous NO ( Chen et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the role of NO to promote Se concentration of rice seedling roots under Se IV supply was confirmed. Our data are consistent with the results of Lehotai et al () in the model plant Arabidopsis thaliana , but differ from those in Brassica rapa , in which Se itself triggered NR and NOS dependent generation of endogenous NO ( Chen et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…Beside plant hormones, nitric oxide has been reported to be a regulator of PAOs in plants . Se stress can modulate endogenous nitric oxide level through positive or negative pathways in plants . Therefore, further studies are needed to reveal the complicated role of nitric oxide in the regulation of PAOs in plants in response to Se stress.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Se generated ROS initiated defense mechanism against Se stress (De Pinto et al, 2012). Previous studies reported that ROS accumulation under Se stress increased lipid peroxidation, cell mortality in Arabidopsis and Vicia faba (Lehotai et al, 2012; Mroczek-Zdyrska and Wójcik, 2012). Apart from plant cells, Wallenberg et al (2010) reported generation of mitochondrial superoxide in human cells under Se stress.…”
Section: Selenium Toxicity In Plantsmentioning
confidence: 91%